MR fingerprinting using the quick echo splitting NMR imaging technique - Jiang, Yun; Ma, Dan; Jerecic, Renate; Duerk, Jeffrey; Seiberlich, Nicole; Gulani, Vikas; Griswold, Mark A. (Magnetic resonance in medicine, 2017)
Purpose The purpose of the study is to develop a quantitative method for the relaxation properties with a reduced radio frequency (RF) power deposition by combining magnetic resonance fingerprinting (MRF) technique with quick echo splitting NMR imaging technique (QUEST). Methods A QUEST‐based MRF sequence was implemented to acquire high‐order echoes by increasing the gaps between RF pulses. Bloch simulations were used to calculate a dictionary containing the range of physically plausible signal evolutions using a range of T1 and T2 values based on the pulse sequence. MRF‐QUEST was evaluated by comparing to the results of spin‐echo methods. The specific absorption rate (SAR) of MRF‐QUEST was compared with the clinically available methods. Results MRF‐QUEST quantifies the relaxation properties with good accuracy at the estimated head SAR of 0.03 W/kg. T1 and T2 values estimated by MRF‐QUEST are in good agreement with the traditional methods. Conclusions The combination of the MRF and the QUEST provides an accurate quantification of T1 and T2 simultaneously with reduced RF power deposition. The resulting lower SAR may provide a new acquisition strategy for MRF when RF energy deposition is problematic. Magn Reson Med 77:979–988, 2017. © 2016 International Society for Magnetic Resonance in Medicine